EPIDEMIOLOGÍA DE LA CISTICERCOSIS PORCINA EN TRES CASERÍOS DE LA PROVINCIA DE ZARUMILLA, TUMBES - Taico U., Felipe (2003)
The study assessed the prevalence of porcine cysticercosis in three villages (IslaNoblecilla, Tutumo and Nuevo Progreso) from Matapalo district, in Tumbes, Peru. Allpigs excepting pregnant sows and piglets younger than two-months old were censusedand ear-tagged, and a blood sample was collected. Antibodies against T. solium weredetermined in serum samples using the Enzime linked Immuno Electro Transfer BlotAssay (EITB). Some risk factors associated with the presence of antibodies againstCysticercus cellulosae were estimated. The total prevalence was 26% (139/534). Prevalencerates were 85/236 (36%), 45/276 (16%) and 9/22 (41%) for Nuevo Progreso, Tutumo andIsla Noblecilla respectively. Variables associated with presence of antibodies were village(P = 0.005) and age (P < 0.001). Information on the number of reaction bands in the EITBassay was used to predict the actual prevalence of T. solium infection in pigs using thebeta-binomial stochastic simulation (@Risk 4.0 software). According to the simulation,90% of the expected prevalences were contained in the 9-15% interval. It was concludedthat T. solium transmission is occurring in both human and porcine populations.